Assessment of Impact of Coronary Artery Calcium On Cardiovascular Risk Stratification in an Indian Cohort - Gaikwad, Abhishek; Khan, Yasmin; Singh, Anupam Kumar (Cardiology and Cardiovascular Medicine, 2019)
Background: Cardiovascular diseases are emerging as a major cause of mortality and disability in India. Coronary artery Calcium (CAC) has been proposed as an additional tool for risk re-stratification for Primary prevention. However, there is a lack of data for its incremental value assessment in Indian patients. Methods: This study included 150 patients presenting with risk factors for Cardiovascular Diseases or Symptoms. 10-year risk of CVD was calculated using risk assessment models Revised American College of Cardiology/American Heart Association (Risk ACC/AHA) and WHO Risk Prediction Charts. CT Angiography and Coronary Artery Calcium Scoring was done in each patient. Results: 48.2 % (28/57) of patients in Statins recommended category (10 yr ASCVD Risk >7.5 %) and 11/17 (64.7%) in Statin Considered group (ASCVD Risk 5-7.5 %) according to guidelines had CAC Zero. 13/75 (17.3 %) of patients in whom statin was not recommended had a non-zero Coronary artery Calcium. A total of 52/150 (34.6%) (Statin not needed with CAC non-zero -13, Statin considered and recommended with CAC zero - 39) would be risk restratified using CAC. Conclusion: One Third Patients would be risk restratified using Coronary Artery Calcium Score as an additional tool to convention Cardiovascular Risk Scores.